Getting to zero : how to work through conflict in your high-stakes relationships - Gaddis, Jayson (Hachette Go, an imprint of Hachette Books, 2021)
"The fastest way to indestructible relationships is to become good at working through conflict, together. Conflicts in our closest relationships are scary because so much is at stake. If the conflict doesn't go well, we could lose our marriage, our family or our job, all connected to our security and survival. So we do just about anything not to lose those relationships, including avoid conflict, betraying ourselves or becoming dishonest. Unresolved conflict affects every single aspect of our lives, from self-confidence to physical and mental health. Jayson Gaddis is a personal trainer for relationships and one of the world's leading authorities on interpersonal conflict. For almost two decades, Gaddis has helped individuals, couples, and teams get to the bottom of their deepest conflicts. He helps people see the wisdom in conflict and how to get to zero-how "clean and clear" we feel with others when we have successfully worked through a disagreement. We get to a place where there is "zero" conflict. In Getting to Zero, Gaddis shows the reader how to stop running away from uncomfortable conversations and instead learn how to work through them. Through funny personal stories, uncomfortable examples, and effective tools and skills, he shows the reader how to move from disconnection to connection, acceptance, and understanding. This method upgrades the old tired and static conflict resolution approaches and offers a fresh, street-level, user-friendly road map on exactly how to work through conflict with the people you care most about"--